Fatal Unusual Miliary Tuberculosis in which a Patient Developed Acute Respiratory Distress Syndrome Induced by Infliximab: An Autopsy Case Report - Miyoshi, Shion; Takasaki, Jin; Mine, Sohtaro; Kono, Masanori; Igari, Toru; Takeda, Yuichiro; Hojo, Masayuki; Sugiyama, Haruhito (Internal Medicine, 2017)
Anti-tumor necrosis factor α (anti-TNFα) agents increase the risk of tuberculosis (TB), but cases are rarely fatal. This report concerns a patient who was undergoing treatment with infliximab and presented with acute respiratory distress syndrome due to miliary TB without a miliary shadow. The findings of a pathological autopsy revealed innumerable granulomas in the organs, and the miliary nodules in the lung consisted of more unstructured granulomas. Anti-TNFα agents are unusual in the presentation of TB. It is important, particularly for patients receiving anti-TNFα agents, to constantly consider the possibility of TB and to prepare for appropriate management.